THE EFFECT OF REMOTE WORK AND WORK-LIFE BALANCE ON EMPLOYEE MOTIVATION: A LITERATURE REVIEW - BOUZAKRAOUI ALAOUI , Salma; EL MARZOUKI , Abdenbi (Revue Internationale des Sciences de Gestion, 2023)
During the Covid-19 crisis the approach of remote work that represents a form of work organization through which the employee performs tasks, outside the premises of the company on a regular and voluntary basis, using information and communication technologies, particularly the Internet (OLLIVIER, 2019) was adopted as an order of work. While the advantages of the method were welcomed by the employees, the emergence of its negative sides also caused some disruption in the work-life balance of employees. The deterioration of the work-life balance has led to changes in the emotions, thoughts, attitudes and behaviors of employees. The point where the changes were most apparent was in employee motivation. The emergence of factors that can affect employee motivation has led to certain difficulties in the workflows and in the achievement of the objectives of the institutions. In this sense, the objective of this study is to analyse through a literature review the changes in work patterns, disruptions in work-life balance and work-life balance and the effects of both on employee motivation during Covid-19.